2023
DOI: 10.3390/molecules28083540
|View full text |Cite
|
Sign up to set email alerts
|

Brewer’s Spent Yeast Cell Wall Polysaccharides as Vegan and Clean Label Additives for Mayonnaise Formulation

Abstract: Brewer’s spent yeast (BSY) mannoproteins have been reported to possess thickening and emulsifying properties. The commercial interest in yeast mannoproteins might be boosted considering the consolidation of their properties supported by structure/function relationships. This work aimed to attest the use of extracted BSY mannoproteins as a clean label and vegan source of ingredients for the replacement of food additives and protein from animal sources. To achieve this, structure/function relationships were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The carbohydrates can act by minimizing emulsion stability by improving protein-protein interactions and developing a multilayer cohesive protein film at the interface that prevents foam collapse and enables the formation of a more stable foam [56,57]. The high protein concentration enhances the amphiphilic character of mannoproteins, thereby improving their overall emulsifying properties [58].…”
Section: Composition Surface Tension and Emulsification Propertymentioning
confidence: 99%
“…The carbohydrates can act by minimizing emulsion stability by improving protein-protein interactions and developing a multilayer cohesive protein film at the interface that prevents foam collapse and enables the formation of a more stable foam [56,57]. The high protein concentration enhances the amphiphilic character of mannoproteins, thereby improving their overall emulsifying properties [58].…”
Section: Composition Surface Tension and Emulsification Propertymentioning
confidence: 99%
“…Mannoprotein's emulsion stability is influenced by salt, and the addition of CaCl 2 will make the emulsion less stable by lowering the electrostatic attraction between the droplets. A study by Reis found that mannoproteins with higher degrees of substitution had better emulsifying properties, suggesting that mannoproteins could be used as emulsifiers in food applications (Reis et al, 2023). Mannoproteins contain hydrophilic sugar sections and a protein portion with hydrophobic and hydrophilic domains that contribute to the quality and stability of the foam.…”
Section: Emulsifying and Foaming Propertymentioning
confidence: 99%
“…Brewer's spent yeast (BSY), a by-product of beer production, represents a vast untapped reservoir of yeast cell wall polysaccharides. It is the second largest beer production byproducts and annually, significant quantities of BSY are disposed of, with current utilization limited to animal feed applications (Ferreira et al, 2010;Reis et al, 2023).…”
Section: Introductionmentioning
confidence: 99%